EXTRACTION POTENTIAL OF DIFFERENT SOLVENTS IN THE STUDY OF ORGANIC MATTER CONCENTRATIONS IN THE ENVIRONMENT - Ben-Awuah, Joel (2013)
The extraction potential of three solvents: dichloromethane, sodium pyrophosphate and dichloromethane:methanol (DCM:MeOH, 93:7 v/v) in extracting organic matter for organic matter type and concentration studies in the environment has been tested. Three sandstone samples were dissolved in the solvents and the extract analyzed using UV-Vis spectrophotometer. Analysis based on the absorbencies of humic acids (E4) and fulvic acids (E6) indicate sodium pyrophosphate as the most potent solvent, followed by dichloromethane and finally DCM:MeOH, 93:7 v/v.